If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 0 = 8z + -1(3 + -1z) 0 = 8z + (3 * -1 + -1z * -1) 0 = 8z + (-3 + 1z) Reorder the terms: 0 = -3 + 8z + 1z Combine like terms: 8z + 1z = 9z 0 = -3 + 9z Solving 0 = -3 + 9z Solving for variable 'z'. Move all terms containing z to the left, all other terms to the right. Add '-9z' to each side of the equation. 0 + -9z = -3 + 9z + -9z Remove the zero: -9z = -3 + 9z + -9z Combine like terms: 9z + -9z = 0 -9z = -3 + 0 -9z = -3 Divide each side by '-9'. z = 0.3333333333 Simplifying z = 0.3333333333
| Cx-Fy=L | | 1/2x+1/5=4(3/4x+4) | | 12-9(y+5)=-(1-y) | | -11+-17= | | 5+7w=15+3w | | 2(2x-2)+2(3x+8)=172 | | .85t+.15(10-t)=8.7 | | 7d+d+1= | | 3-2x+4+6=9 | | 10-(n-10)=5(n+3) | | 2(2x-2)+2(3x-8)=172 | | 1/4+x=-3/4 | | 1-1/5x=-4/5(5+x) | | -3+4k=3-6+3k | | 6x^2+2y=9xy-7 | | 2x=2(2+x) | | -5/6+2/5 | | 24-21/2=x | | (2x-2)+(3x-8)=172 | | 2n+9=6n | | 16f=15f+2 | | -10x^2-65x-75=0 | | 10-3r+5+2r= | | h(t)=V*t-16*t^2 | | x-(x+17)=2(11-3x) | | 5=v/20 | | x+6=3-2 | | W-w=3 | | 5n=250 | | 7x+1=15x+3 | | 2(x+3)=6(3) | | f+g/2 |